2004
DOI: 10.1007/s11661-004-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification of high-density polyethylene by direct current and radio frequency glow discharge on wetting and adhesion characteristics

Abstract: The present investigation aims to optimize the process parameters of Direct Current (DC) and Radio Frequency (RF) glow discharge treatment through air in terms of discharge power and time of exposure for the surface modification of high-density polyethylene (HDPE) sheet, for attaining best adhesive joint of the polymer to mild steel. In order to estimate the extent of surface modification, the surface energies of the polymer surfaces exposed to glow discharge have been determined by measuring contact angles us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…In addition the root mean square (RMS) roughness of untreated surface was 0.68 nm which got increased rapidly up to 14.13 nm when treated in air plasma. These morphological changes may be due to the removal of top few monolayers of the polymer film, caused by the bombardment of plasma particles on the surface of PET film [2,12]. This resulted in an apparent increase in the surface roughness causing improvement in wettability and bonding strength.…”
Section: Morphological and Compositional Analysis: Afm And Xps Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition the root mean square (RMS) roughness of untreated surface was 0.68 nm which got increased rapidly up to 14.13 nm when treated in air plasma. These morphological changes may be due to the removal of top few monolayers of the polymer film, caused by the bombardment of plasma particles on the surface of PET film [2,12]. This resulted in an apparent increase in the surface roughness causing improvement in wettability and bonding strength.…”
Section: Morphological and Compositional Analysis: Afm And Xps Resultsmentioning
confidence: 99%
“…The introduction of oxygen containing polar groups on the polymer surface may be the main reason for the hydrophilic improvement. Since PET films were treated in air plasma, it is obvious that some nitrogen-containing group will be incorporated onto the surface [2,4,9]. For untreated polymer films, there is no N1s peak but for plasma treated one, there appears to be a small N1s peak.…”
Section: Morphological and Compositional Analysis: Afm And Xps Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Recently, studies on improving surface wettability on PP films using various surface modification techniques have been reported. 8,9 In the present study DC glow discharge 10 was employed to study the effect on the surface energy as well as resistivity of a thin 100 mm film of PP. The surface energy of liquid adhesives and polymers is about 100 mJ/m 2 , while for ceramics and metals it is about 500 mJ/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that treatment in an oxygen-containing plasma resulted in the buildup of polar oxygen-containing groups on the surface. This treatment significantly increases the surface energy of PE and improved its wettability and adhesion characteristics [4][5][6][7][8][9][10]. Ponomarev et al [11][12][13][14][15] studied in detail the formation of radicals, double bonds, and intermolecular crosslinks and hydrogen evolution during the treatment of PE in air, hydrogen, and helium plasmas.…”
mentioning
confidence: 99%